Strength and durability of roller compacted concrete with different types and addition rates of polypropylene fibers - Kilic, Ismail; Gokce Gok, Saadet (Revista de la Construcción. Journal of Construction, 2021)
Roller compacted concrete (RCC) is a relatively new alternative construction material that can be used in road and dam constructions by allowing rapid use after production and the use of conventional building materials in production. RCC, which can be produced with low water/cement ratio, is one of the rigid road pavement types and shows similarity to flexible road pavements with the production technique. Different types of fibers such as steel and polypropylene (PP) are used in concrete roads with the aim of preventing cracks, reducing the pavement thickness and increasing the permissible joint gap. In this study, flexural strength, compressive strength, unit weight, water absorption, ultrasonic pulse velocity, modulus of elasticity and freeze-thaw resistance were determined in roller compacted concretes produced by using two different polypropylene-based fibers. In RCC design, fiber addition was insufficient to improve concrete properties in terms of strength and durability. It has been observed that there was a 14.4% reduction in compressive strength with 0.20% fiber inclusion, and a 46.8% reduction in compressive strength with 0.50% fiber inclusion. Polypropylene fiber inclusion increased the water absorption percentages and decreased the specific weights of fiber reinforced roller compacted concretes. However, roller compacted concretes produced with PP-fiber exhibited a good performance under freeze-thaw attack.